NiMn-based polycrystalline alloy and preparation method and application thereof

Through the spray casting and uniform annealing treatment process, the problems of complex preparation processes and poor magneto-thermal performance of existing NiMn-based magnetic refrigeration materials are solved, and efficient and controllable magnetic refrigeration performance is achieved, which broadens the application range.

CN119615374AActive Publication Date: 2025-03-14GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411809690.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing NiMn-based magnetic refrigeration materials have complex preparation processes and poor magneto-thermal performance, making it difficult to achieve simple and controllable high-efficiency magnetic refrigeration.

Method used

The spray casting process is used to quickly solidify the NiMn-based alloy, and the internal defects of the grain are reduced through uniform annealing treatment, the degree of homogenization is improved, and the rapid occurrence of martensite phase transformation is achieved, and the magneto-thermal performance is improved through the coupling of magnetic phase transformation and structural phase transformation.

Benefits of technology

The high magneto-thermal performance of NiMn-based polycrystalline alloy is achieved, the preparation process is simplified, the controllability of performance is improved, and the application range of it in magnetic refrigeration technology is broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615374A_ABST
    Figure CN119615374A_ABST
Patent Text Reader

Abstract

The invention provides a NiMn-based polycrystalline alloy as well as a preparation method and application thereof. The preparation method of the NiMn-based polycrystalline alloy comprises the following steps: casting an alloy raw material to obtain an as-cast alloy, performing spray casting on the as-cast alloy to obtain a polycrystalline alloy cast ingot, and performing homogenizing annealing treatment on the polycrystalline alloy cast ingot to obtain the NiMn-based polycrystalline alloy. The preparation process provided by the invention is simple and controllable, the prepared NiMn-based polycrystalline alloy is few in internal defects and high in homogenization degree, rapid occurrence of martensite phase transformation can be realized, and the magnetocaloric performance of the NiMn-based polycrystalline alloy is improved through coupling of magnetic phase transformation and structural phase transformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of Heusler alloy material processing, and specifically relates to a ferromagnetic shape memory alloy material, and in particular to a NiMn-based polycrystalline alloy and a preparation method and application thereof. Background Art

[0002] Environment and energy have always been hot issues that people are concerned about. In order to alleviate the burden of the greenhouse effect on the environment and respond to the advocacy of energy conservation, emission reduction and green environmental protection, it has become an urgent need for the industry to develop a new refrigeration technology that can replace traditional gas compression refrigeration technology.

[0003] Magnetic refrigeration is a refrigeration technology based on the magnetocaloric effect (MCE) that has the potential to be highly efficient and environmentally friendly. MCE refers to the phenomenon that the temperature of certain materials changes reversibly under the action of a magnetic field, which is usually significant in rare earth elements, ferromagnetic materials, and magnetic alloys. Compared with traditional gas compression refrigeration, magnetic refrigeration does not emit greenhouse gases such as Freon, and in theory has higher energy efficiency, making it a research hotspot for the next generation of green refrigeration technology.

[0004] At present, Ni-Mn-based Heusler alloys have attracted widespread attention due to their large MCE, adjustable martensitic phase transition temperature and good chemical stability. In particular, alloy materials such as Ni-Co-Mn-Ti alloys have broad application prospects because they can optimize martensitic phase transition behavior and magnetocaloric effect by regulating composition and process. During the alloy preparation process, microstructural characteristics such as grain size, phase interface characteristics, and defect concentration have a significant impact on its magnetic refrigeration performance. Studying these microscopic factors is crucial to improving the performance of magnetic refrigeration materials.

[0005] CN112760535A discloses a magnetic refrigeration material and a preparation method thereof, which uses a high-abundance rare earth element R to replace Ni, Co, Mn, and Ti, and can effectively regulate the phase change temperature. The material preparation method is as follows: weigh high-purity raw materials according to the stoichiometric ratio of the chemical formula and mix them evenly; then use arc melting or pulling method or directional solidification method to prepare the raw materials into magnetic phase change materials; arc melt the high-purity raw materials under argon protection to obtain block samples; finally, vacuum melt quench part of the block samples obtained by arc melting to obtain thin strips or vacuum annealing. The phase change temperature is regulated in a wide temperature range of 100 to 350K as the content of high-abundance rare earth elements increases, and an enhanced magnetocaloric effect is obtained.

[0006] CN112216458A discloses a material for enhancing magnetocaloric effect and a preparation method thereof. The chemical formula of the material is Ni 35 Co 15 Mn 35-x P x Qy , where \(0\leq x\leq12\), \(10\leq y\leq22\), \(P\) is one of the transition elements \(Ti\), \(V\), \(Cr\), \(Mn\), \(Fe\), \(Co\), \(Ni\), \(Cu\), \(Zn\), and \(Q\) is one of \(Sc\), \(Ti\), \(Zr\), \(Hf\), \(V\), \(Nb\), \(Ta\). Weigh high-purity raw materials according to the above chemical formula ratio, and then use arc melting or the Czochralski method or the directional solidification method under argon protection to obtain a bulk sample with the chemical formula ratio. The bulk sample is subjected to melt spinning under vacuum to obtain a thin strip material with a phase change or directly annealed under vacuum. Then, isostatic pressing is applied to further regulate the phase change and magnetism, so that the magnetic phase change at a lower temperature is regulated to room temperature and above, and at the same time, the enhanced magnetocaloric effect is obtained.

[0007] CN105986322A discloses a magnetic phase change material. The raw materials are prepared into a magnetic phase change material by the Czochralski method or the zone melting method or the directional solidification method. Its chemical formula is: Ni a-m Mn b-n Co m+n Ti c ; where \(a + b + c = 100\), \(20 < a\leq90\), \(5\leq b < 50\), \(5\leq c\leq30\), \(0\leq m\leq a\), \(0\leq n\leq b\), \(0 < m + n < a + b\), and \(a\), \(b\), \(c\), \(m\), and \(n\) represent atomic percentage contents alone or in combination. This magnetic phase change material has high strength and toughness, high deformation rate, strong magnetism, and the characteristic of magnetic field-driven martensitic phase change.

[0008] All the NiMn-based magnetic refrigeration materials disclosed in the prior art require complex melting processes or means such as directional solidification to achieve, and the preparation process is cumbersome. Therefore, it is of great significance to provide a NiMn-based magnetic refrigeration material with a simple and controllable process and excellent magnetothermal performance. Summary of the Invention

[0009] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a NiMn-based polycrystalline alloy and its preparation method and application. The preparation process of the NiMn-based polycrystalline alloy provided by the present invention is simple and controllable. The obtained NiMn-based polycrystalline alloy has few defects inside the grains and high homogenization degree, and can realize the rapid occurrence of martensitic phase change. The magnetothermal performance of the NiMn-based polycrystalline alloy is improved through the coupling of magnetic phase change and structural phase change.

[0010] To achieve the purpose of this invention, the present invention adopts the following technical solutions:

[0011] In the first aspect, the present invention provides a preparation method of a NiMn-based polycrystalline alloy. The preparation method includes:

[0012] Melting and casting alloy raw materials to obtain a cast alloy, spray-casting the cast alloy to obtain a polycrystalline alloy ingot, and performing homogenization annealing treatment on the polycrystalline alloy ingot to obtain the NiMn-based polycrystalline alloy.

[0013] In the present invention, "polycrystalline alloy" refers to an alloy material composed of multiple crystal grains, each crystal grain has a regular atomic arrangement inside, and there are grain boundaries between different crystal grains.

[0014] The present invention uses a spray-casting method to achieve rapid solidification of the NiMn-based polycrystalline alloy, and through a homogenization annealing treatment, reduces the internal defects of the grains, improves the degree of homogenization, and achieves a rapid occurrence of martensitic phase transformation. The magnetocaloric properties of the NiMn-based polycrystalline alloy are improved through the coupling of magnetic phase transformation and structural phase transformation.

[0015] In the present invention, the cast alloy is obtained by melting alloy raw materials through a conventional melting and casting process, and the melting and casting method is not particularly limited.

[0016] The spray casting described in the present invention refers to forming a solid material by spraying molten metal or alloy onto a cooled substrate or mold using the spraying and rapid cooling of liquid metal.

[0017] The present invention changes the phase transition temperature of the NiMn-based polycrystalline alloy by precisely designing the components of the NiMn-based alloy, adjusting the elemental composition, and combining the processes of spray casting and homogenization annealing treatment to achieve coverage of the entire temperature range, further improve its magnetocaloric properties, and broaden the application range of the NiMn-based polycrystalline alloy.

[0018] Preferably, in terms of atomic percentage, the composition of the alloy raw material includes:

[0019]

[0020] X includes any one of Sc, Y, Ce, Dy, or Nd, or a combination of at least two of them.

[0021] In the raw materials for preparing the NiMn-based polycrystalline alloy of the present invention, the Co element can increase the magnetism of the alloy and improve the saturation magnetization intensity of austenite; the Ti element can adjust the phase transition temperature of martensite and form a stable compound to improve the thermal stability of the alloy; and the X element can form a fine precipitated phase to improve the strength and hardness of the alloy.

[0022] In the preparation method provided by the present invention, the alloy raw material includes 35%-37% Ni element, for example, it can be 35%, 35.1%, 35.2%, 35.3%, 35.4%, 35.5%, 35.6%, 35.7%, 35.8%, 35.9%, 36%, 36.1%, 36.2%, 36.3%, 36.4%, 36.5%, 36.6%, 36.7%, 36.8%, 36.9% or 37%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] In the preparation method provided by the present invention, the alloy raw material includes 33%-42% of Mn element, for example, it can be 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5% or 42%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] In the preparation method provided by the present invention, the alloy raw material includes 13%-15% Co element, for example, it can be 13%, 13.1%, 13.2%, 13.3%, 13.4%, 13.5%, 13.6%, 13.7%, 13.8%, 13.9%, 14%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9% or 15%, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0025] In the preparation method provided by the present invention, the alloy raw material includes 8%-17% Ti element, for example, it can be 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5% or 17%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] In the preparation method provided by the present invention, the alloy raw material includes 0%-5% of the X element, for example, it can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. X includes any one or a combination of at least two of Sc, Y, Ce, Dy or Nd, and typical but non-limiting combinations include Sc and Y, Ce and Dy, or Y and Nd.

[0027] In the present invention, the pressure of spray casting affects the supercooling degree during the solidification process of the NiMn-based polycrystalline alloy, thereby affecting the average grain size of the NiMn-based polycrystalline alloy. If the spray casting pressure is too small, the supercooling degree is too small, resulting in excessive grain growth. At the same time, the metal particles sprayed under low pressure do not have enough kinetic energy to complete a sufficient cooling and solidification process, resulting in poor density of the casting and easy formation of defects such as pores and shrinkage cavities. If the spray casting pressure is too high, on the one hand, it may cause molten metal to splash, affecting the homogenization of the NiMn-based polycrystalline alloy. At the same time, the metal droplets may be entrained with bubbles during flight, resulting in pores, bubbles or other defects inside the casting. On the other hand, it leads to excessive supercooling and too small average grain size.

[0028] Preferably, the injection molding pressure is 0.1MPa-2MPa, for example, it can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1MPa, 1.1MPa, 1.2MPa, 1.3MPa, 1.4MPa, 1.5MPa, 1.6MPa, 1.7MPa, 1.8MPa, 1.9MPa or 2MPa, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.2MPa-1MPa.

[0029] Preferably, the spray-casting is performed under a protective atmosphere.

[0030] Preferably, the protective atmosphere comprises an inert gas.

[0031] Preferably, the temperature of the homogenization annealing treatment is 600°C-1100°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the homogenization annealing treatment time is 3h-168h, for example, it can be 3h, 5h, 10h, 20h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, 108h, 120h, 132h, 144h, 156h or 168h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the cooling medium for the homogenization annealing treatment includes any one of water, ice-water mixture or liquid nitrogen, or a combination of at least two of them.

[0034] The average grain size of NiMn-based polycrystalline alloys affects the martensite phase transition temperature and the severity of the phase transition. If the grains are too large, the number of grain boundaries will decrease and martensite nucleation will be difficult. If the grains are too small, the grain refinement can enhance the interaction between grain boundaries. The grain boundaries will hinder the phase transition process and inhibit the occurrence of martensite phase transition.

[0035] Preferably, after the homogenization annealing treatment, the average grain size of the NiMn-based polycrystalline alloy is 100μm-1000μm, for example, it can be 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, 550μm, 600μm, 650μm, 700μm, 750μm, 800μm, 850μm, 900μm, 950μm or 1000μm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 150μm-500μm.

[0036] Preferably, the preparation method further comprises powdering the NiMn-based polycrystalline alloy;

[0037] Preferably, the powdering treatment method includes ball milling, impact crushing, air flow milling, spray drying and atomization.

[0038] In a second aspect, the present invention provides a NiMn-based polycrystalline alloy, wherein the NiMn-based polycrystalline alloy is prepared by the preparation method described in the first aspect.

[0039] Preferably, the composition of the NiMn-based polycrystalline alloy includes Ni: 35%-37%, Mn: 33%-42%, Co: 13%-15%, Ti: 8%-17% and X: 0-5%.

[0040] The NiMn-based polycrystalline alloy provided by the present invention includes 35%-37% of Ni element, for example, it can be 35%, 35.1%, 35.2%, 35.3%, 35.4%, 35.5%, 35.6%, 35.7%, 35.8%, 35.9%, 36%, 36.1%, 36.2%, 36.3%, 36.4%, 36.5%, 36.6%, 36.7%, 36.8%, 36.9% or 37%, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0041] In the preparation method provided by the present invention, the alloy raw material includes 33%-42% of Mn element, for example, it can be 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5% or 42%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] In the preparation method provided by the present invention, the alloy raw material includes 13%-15% Co element, for example, it can be 13%, 13.1%, 13.2%, 13.3%, 13.4%, 13.5%, 13.6%, 13.7%, 13.8%, 13.9%, 14%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9% or 15%, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0043] In the preparation method provided by the present invention, the alloy raw material includes 8%-17% Ti element, for example, it can be 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5% or 17%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] In the preparation method provided by the present invention, the alloy raw material includes 0%-5% of the X element, for example, it can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0045] Preferably, the average grain size of the NiMn-based polycrystalline alloy is 100-1000 μm, for example, it can be 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm or 1000 μm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 150 μm-500 μm.

[0046] In a third aspect, the present invention provides an application of a NiMn-based polycrystalline alloy, wherein the NiMn-based polycrystalline alloy is applied in the field of magnetic refrigeration technology.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The preparation method provided by the present invention can comprehensively optimize the magnetocaloric properties of NiMn-based polycrystalline alloys. The present invention adopts a process of spray casting combined with homogenization annealing treatment, combines three mechanisms of alloying, rapid solidification and homogenization, and comprehensively optimizes the magnetocaloric properties of NiMn-based polycrystalline alloys. Through rapid solidification means, internal defects of grains after annealing can be reduced, and the average size of grains can be adjusted to improve the degree of homogenization, so as to achieve a rapid occurrence of martensitic phase transformation, and improve the magnetocaloric properties of NiMn-based polycrystalline alloys through the coupling of magnetic phase transformation and structural phase transformation. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 1 is the XRD spectrum of the NiMn-based polycrystalline alloys prepared in Examples 1 to 3 and Comparative Example 1.

[0050] Figure 2 This is a SEM image of the NiMn-based polycrystalline alloy prepared in Example 1.

[0051] Figure 3 This is a SEM image of the NiMn-based polycrystalline alloy prepared in Example 2.

[0052] Figure 4 This is a SEM image of the NiMn-based polycrystalline alloy prepared in Example 3.

[0053] Figure 5 It is a MT curve diagram of the NiMn-based polycrystalline alloys prepared in Examples 1 to 3 and Comparative Example 1 under a 0.2T magnetic field change.

[0054] Figure 6 MH curve of the NiMn-based polycrystalline alloy prepared in Example 1.

[0055] Figure 7 It is the MH curve of the NiMn-based polycrystalline alloy prepared in Example 2.

[0056] Figure 8 It is the MH curve of the NiMn-based polycrystalline alloy prepared in Example 3.

[0057] Fig. 9 This is the MH curve of the NiMn-based polycrystalline alloy prepared in Comparative Example 1.

[0058] Fig.10 It is the MH curve of the NiMn-based polycrystalline alloy prepared in Example 4.

[0059] Fig.11 This is the MH curve of the NiMn-based polycrystalline alloy prepared in Comparative Example 2.

[0060] Fig.12 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Example 1.

[0061] Fig.13 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Example 2.

[0062] Fig.14 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Example 3.

[0063] Fig.15 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Comparative Example 1.

[0064] Fig.16 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Example 4.

[0065] Fig.17 This is the magnetic entropy change ΔSM diagram of the NiMn-based polycrystalline alloy prepared in Comparative Example 2.

[0066] Fig.18 It is a comparison diagram of the magnetic entropy change ΔSM of the NiMn-based polycrystalline alloys prepared in Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] Example 1

[0069] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy, the preparation method comprising:

[0070] Configuration composition is Ni 36 Co 13 Mn 35 Ti 16 The alloy raw material (at.%) is smelted into a cast alloy by an arc melting furnace. The cast alloy is spray-casted under Ar protection at a pressure of 0.3 MPa. The spray-cast ingot is subjected to a homogenization annealing treatment at a temperature of 1050°C for 96 hours and a cooling method of water quenching to obtain the Ni 36 Co 13 Mn 35 Ti 16 Polycrystalline alloy.

[0071] The Ni prepared in this example 36 Co 13Mn 35 Ti 16 The polycrystalline alloy is austenite at room temperature, as shown in the SEM image. Figure 2 As shown, the average grain size is 157 μm, and the XRD diffraction pattern is as follows Figure 1 shown.

[0072] Example 2

[0073] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy, the preparation method comprising:

[0074] Configuration composition is Ni 35 Co 15 Mn 42 The alloy raw material of Ti8 (at.%) is smelted into a cast alloy by an arc melting furnace. The cast alloy is sprayed under Ar protection with a spraying pressure of 0.1 MPa. The sprayed ingot is subjected to a homogenization annealing treatment at a temperature of 700°C for 120 hours and quenched with an ice-water mixture to obtain the Ni 35 Co 15 Mn 42 Ti8 polycrystalline alloy.

[0075] The Ni prepared in this example 35 Co 15 Mn 42 Ti8 polycrystalline alloy is austenite at room temperature, SEM image is as follows Figure 3 As shown, the average grain size is 249.2 μm, and the XRD diffraction pattern is as follows Figure 1 shown.

[0076] Example 3

[0077] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy, the preparation method comprising:

[0078] Configuration composition is Ni 36 Co 14 Mn 40 Ti 12 The alloy raw material (at.%) is smelted into a cast alloy by an arc melting furnace. The cast alloy is spray-casted under Ar protection at a pressure of 1 MPa. The spray-cast ingot is subjected to homogenization annealing at a temperature of 900°C for 108 hours and cooled with liquid nitrogen to obtain the Ni 36 Co 14 Mn 40 Ti 12 Polycrystalline alloy.

[0079] The Ni prepared in this example 36 Co 14 Mn40 Ti 12 The polycrystalline alloy is austenite at room temperature, as shown in the SEM image. Figure 4 As shown, the average grain size is 461.2 μm, and the XRD diffraction pattern is as follows Figure 1 shown.

[0080] Example 4

[0081] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy, the preparation method comprising:

[0082] Configuration composition is Ni 37 Co 13 Mn 34 Ti 15.75 Sc 0.25 The alloy raw material (at.%) is smelted into a cast alloy by an arc melting furnace. The cast alloy is spray-casted under Ar protection at a pressure of 1.5 MPa. The spray-cast ingot is subjected to a homogenization annealing treatment at a temperature of 1050°C for 96 hours and a cooling method of water quenching to obtain the Ni 37 Co 13 Mn 34 Ti 15.75 Sc 0.25 Polycrystalline alloy.

[0083] Example 5

[0084] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy. The preparation method is the same as that of Embodiment 1 except that the injection molding pressure is 0.05 MPa.

[0085] Example 6

[0086] This embodiment provides a method for preparing a NiMn-based polycrystalline alloy. The preparation method is the same as that of Embodiment 1 except that the injection molding pressure is 3 MPa.

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing a NiMn-based polycrystalline alloy, comprising:

[0089] Configuration composition is Ni 37 Co 13 Mn 34 Ti 15.75 Sc 0.25 The alloy raw material with (at.%) is smelted into cast titanium alloy by an arc melting furnace, and the cast alloy is subjected to homogenization annealing treatment at a temperature of 1050°C for 96 hours, and the cooling method is water quenching.

[0090] The Ni prepared in this comparative example 37 Co13 Mn 34 Ti 15.75 Sc 0.25 The polycrystalline alloy is in the austenite phase at room temperature, and the XRD diffraction pattern is as follows Figure 1 shown.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a NiMn-based polycrystalline alloy, comprising:

[0093] Configuration composition is Ni 36 Co 13 Mn 35 Ti 16 The alloy raw material with (at.%) is smelted into cast titanium alloy by an arc melting furnace, and the cast alloy is subjected to homogenization annealing treatment at a temperature of 1050°C for 96 hours, and the cooling method is water quenching.

[0094] Performance Test:

[0095] The magnetocaloric properties of the NiMn-based polycrystalline alloys prepared in all the above examples and comparative examples were tested. The test method was as follows: when measuring the MT curve, the test interval was 50-390K, and the heating rate and cooling rate were both 3K·min -1 , a constant magnetic field of 0.2 T was applied; during the measurement of the MH curve, the rate of magnetic field reduction was 200 Oe·s -1 In the process of testing the MH curve, the MH near the phase transition temperature (±20K) is tested using the loop method, that is, recording two cycles of rising magnetic field-falling magnetic field-rising magnetic field-falling magnetic field.

[0096] The test results are shown in Table 1.

[0097] Table 1

[0098] <![CDATA[Magnetic entropy / J·kg -1 ·K -1 > Martensitic transformation temperature / K Example 1 35.2 189.1 Example 2 45.2 180.15 Example 3 49.4 169.9 Example 4 24.11 283 Example 5 22.7 197.9 Example 6 20.8 183.7 Comparative Example 1 18.1 211 Comparative Example 2 17.83 230

[0099] According to the data results of Examples 1 to 3 and Comparative Example 1, the present invention comprehensively optimizes the magnetocaloric properties of the NiMn-based polycrystalline alloy by first spray-casting the cast alloy and then performing homogenization annealing through three mechanisms of alloying, rapid solidification and homogenization. The internal defects of the grains after annealing are reduced by rapid solidification. The average size of the grains is controlled to improve the degree of homogenization and achieve a rapid occurrence of martensitic phase transformation. The magnetocaloric properties of the NiMn-based polycrystalline alloy are improved through the coupling of magnetic phase transformation and structural phase transformation.

[0100] like Figure 2As shown, by combining the process of spray casting and homogenization annealing, the phase transition temperature of the Ni-Co-Mn-Ti-based polycrystalline alloy prepared by the present invention is reduced from 211K to 169.9K, achieving controllable adjustment in the low temperature zone. The phase transition temperature of the Ni-Co-Mn-Ti-X-based polycrystalline alloy prepared in the present invention is increased from 230K to 283K, achieving controllable adjustment in the higher temperature zone, that is, the present invention designs the components of the NiMn-based polycrystalline alloy and combines the spray casting and homogenization annealing process to achieve full-temperature controllable adjustment of the phase temperature of the NiMn-based polycrystalline alloy. The magnetic entropy of the NiMn-based polycrystalline alloy prepared by the present invention can reach 49.54J·kg -1 ·K -1 .

[0101] like Figure 6-Figure 9 Compared with the NiMn-based polycrystalline alloy prepared in Comparative Example 1, under a 5T magnetic field change, the phase transition temperature of the NiMn-based polycrystalline alloy prepared in Example 1 decreases from 211K to 189.1K. The phase transition temperatures of the NiMn-based polycrystalline alloys prepared in Example 2 and Example 3 decrease to 180.15K and 169.9K, respectively.

[0102] like Figure 10-11 Compared with the NiMn-based polycrystalline alloy prepared in Comparative Example 2, the phase transition temperature of the NiMn-based polycrystalline alloy prepared in Example 4 is increased from 230K to 283K under a 5T magnetic field change.

[0103] like Figure 12-Figure 15 Compared with the NiMn-based polycrystalline alloy prepared in Comparative Example 1, the magnetic entropy of the NiMn-based polycrystalline alloy prepared in Example 1 increased from 18.1 J·kg -1 ·K -1 Increased to 35.2 J·kg -1 ·K -1 The magnetic entropy of the NiMn-based polycrystalline alloy prepared in Example 2 and Example 3 was increased to 45.2 J·kg -1 ·K -1 and 49.4 J·kg -1 ·K -1 .

[0104] like Figure 16-Figure 17 Compared with the NiMn-based polycrystalline alloy prepared in Comparative Example 2, the magnetic entropy of the NiMn-based polycrystalline alloy prepared in Example 4 increased from 17.83 J·kg to -1 ·K -1 Increased to 24.11 J·kg -1 ·K -1 .

[0105] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a NiMn-based polycrystalline alloy, characterized in that: The preparation method comprises: The alloy raw material is melted to obtain a cast alloy, the cast alloy is spray-cast to obtain a polycrystalline alloy ingot, and the polycrystalline alloy ingot is subjected to homogenization annealing treatment to obtain the NiMn-based polycrystalline alloy.

2. The preparation method according to claim 1, characterized in that In terms of atomic percentage, the composition of the alloy raw material includes: X includes any one of Sc, Y, Ce, Dy, or Nd, or a combination of at least two of them.

3. The preparation method according to claim 1 or 2, characterized in that: The injection-casting pressure is 0.1MPa-2MPa, preferably 0.2MPa-1MPa; Preferably, the spray casting is carried out under a protective atmosphere; Preferably, the protective atmosphere comprises an inert gas.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the homogenization annealing treatment is 600°C-1100°C; Preferably, the homogenization annealing treatment time is 3h-168h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The cooling medium for the homogenization annealing treatment includes any one of water, ice-water mixture or liquid nitrogen, or a combination of at least two of them.

6. The preparation method according to any one of claims 1 to 5, characterized in that: After the homogenization annealing treatment, the average grain size of the NiMn-based polycrystalline alloy is 100 μm-1000 μm, preferably 150 μm-500 μm.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method further comprises pulverizing the NiMn-based polycrystalline alloy; Preferably, the powdering treatment method includes ball milling, impact crushing, air flow milling, spray drying and atomization.

8. A NiMn-based polycrystalline alloy, characterized in that: The NiMn-based polycrystalline alloy is prepared by the preparation method according to any one of claims 1 to 7.

9. The NiMn-based polycrystalline alloy according to claim 8, characterized in that: The components of the NiMn-based polycrystalline alloy include Ni: 35%-37%, Mn: 33%-42%, Co: 13%-15%, Ti: 8%-17% and X: 0-5%; Preferably, the average grain size of the NiMn-based polycrystalline alloy is 100 μm-1000 μm, preferably 150-500 μm.

10. An application of a NiMn-based polycrystalline alloy, characterized in that: The NiMn-based polycrystalline alloy is applied in the field of magnetic refrigeration.

Citation Information

Patent Citations

  • Magnetic phase change material

    CN105986322A

  • Magnetocaloric effect enhancing material and preparation method thereof

    CN112216458A

  • Magnetic refrigeration material and preparation method thereof

    CN112760535A

  • Mn50CoxNiySnz high-temperature ferromagnetic shape memory alloy material and preparation methods thereof

    CN102115914A

  • Nickel-based alloy with high-elastic thermal stability and preparation method and application thereof

    CN107586999A